THE ROLE OF TEACHERS AND PARENTS IN LEARNING AKHLAK DURING THE COVID-19 PANDEMIC IN MTsN 2 PASAMAN: CASE STUDY OF LEARNERS' LEARNING INTERESTS - Maimun Maimun; Ahmad Lahmi; Syaflin Halim (Program Pascasarjana UMSB, 2021)
Researchers found problems in the practice of the role of teachers and parents during online learning for students. Based on these conditions, the role of teachers and parents becomes what students need during learning. Therefore, the author raised this qualitative research with the title `The Role of Teachers and Parents in Learning Morals during the Covid-19 Pandemic at MTsN 2 Pasaman: A Case Study of Student Interest in Learning.` Problem formulation: (1) What is the role of teachers and other people? parents in online learning of morals during the covid 19 pandemic to students of MTsN 2 Pasaman? (2) What is the role of teachers and parents in fostering interest in religious learning, especially moral aqidah to students of MTsN 2 Pasaman? to students of MTsN 2 Pasaman. (2) The role of teachers and parents in cultivating interest in learning Islam, especially the moral creed towards the students of MTsN 2 Pasaman.Research method: This study uses a descriptive qualitative approach. Descriptive research aims to make research results real, accurate, and systematic about a series of real events and characteristics of certain regions and communities. Data collection techniques apply interview, observation, and documentation methods. The results of this study were determined by the level of knowledge, the presence of parents, and interaction. So, students who have parents with religious knowledge are also good, and are more at home, then the role of parents can be given as a whole in learning morals. On the other hand, students who have parents with less knowledge or religious knowledge, and are busy working, have a limited role in learning activities for their children's morals and beliefs. Parents provide motivation, messages, advice, sanctions (punishments) and rewards (rewards) to their children. This is done to foster interest in learning the religion of their children who study at school or at home. Therefore, parents have performed their roles as motivators, educators, discipline enforcers, and regulators or controllers. All of these roles are carried out differently for each parent, depending on the level of knowledge and religious basis, as well as the intensity of the meeting between parents and children in interacting while at home.